Pengaruh Intervensi PerawatanLuka Perineum Pada Ibu Nifas dengan NaCl 0,9%: a Case Report - Aulia, Dian; Solehati, Tetti; Sukmawati, Sukmawati (Nursing Sciences Journal, 2023)
Background: Perineal rupture in postpartum women is a common occurrence. The number of mothers and families who do not pay attention to the importance of postpartum care causes the healing process of perineal wounds to be hampered and susceptible to infection. Objective: To describe the effect of perineal wound care intervention with NaCl 0.9% on postpartum women. Methods: This research is a descriptive case study with a nursing care approach method in postpartum women who experience perineal wounds with the main nursing problem of infection risk and are given perineal wound care interventions with NaCl 0.9% with analysis of results using observation of signs of infection using REEDA. Results: After the intervention was given there was an improvement in the condition of the perineal wound, no infection occurred and the ability to perform perineal care in patients increased. Conclusion: The results of this case study show that the provision of perineal wound care using NaCl 0.9% in postpartum women helps to improve perineal wound healing so as to avoid the risk of infection.